Vertical integration in a multi-level governance system using the example of the German Resource Efficiency Programme. - (:unkn) unknown (Routledge; Taylor & Francis, 2021)
The ultimate goal of German Resource Efficiency Programme (ProgRess) is to make the extraction and use of natural resources more sustainable and reduce associated environmental pollution as much as possible. By doing this - also with responsibility towards future generations - the programme should create a prerequisite for securing a long-term high quality of life. To bring the policy approaches formulated in ProgRess to reality, efforts to implement resource efficiency measures have to be increased at all levels - from international to regional to local. The chapter intends to provide an impetus for the current debate on ProgRess policy development. The chapter identifies, analyses and describes deficits and possibilities of vertical integration of the German programme in particular and derives recommendations for action which may also serve as indications for other strategies. The following sections are based on results of the advisory report "Vertical integration of the national resource efficiency programme ProgRess (VertRess)", conducted by the German Institute of Urban Affairs (Difu) and the Wuppertal Institute for Climate, Environment and Energy on behalf of the German Environmental Agency (UBA) and the Federal Ministry of the Environment, Nature Conservation and Nuclear Safety (BMU).
Keywords: Deutsches Ressourceneffizienzprogramm (ProgRess); Sustainable Development Goals; Ressourcenverbrauch; Ressourcenschonung; Ressourcenschutz; Klimaschutz; Bundesprogramm